Perceptions of adolescents and young adults with allergy and/or asthma and their parents on EAACI guideline recommendations about transitional care: A European survey. Issue 4 (1st November 2021) - Khaleva, Ekaterina; Knibb, Rebecca; DunnGalvin, Audrey; Vazquez‐Ortiz, Marta; Comberiati, Pasquale; Alviani, Cherry; Garriga‐Baraut, Teresa; Gowland, Mary Hazel; Gore, Claudia; Angier, Elizabeth; Blumchen, Katharina; Duca, Bettina; et al.
Abstract: Background: The European Academy of Allergy and Clinical Immunology has developed a guideline to provide evidence‐based recommendations for healthcare professionals to support the transitional care of adolescents and young adults (AYA) with allergy and/or asthma. The goal of this work was to ensure that the draft recommendations are also important for patients. Methods: We surveyed patients aged 11–25 years with allergy and/or asthma and their parents across Europe between 17 February and 16 March 2020. The multilingual survey was distributed through national allergy and asthma patient organizations in Europe as well as through social media. Results: A total of 1210 responses from 24 European countries were collected. There were 415 (34.3%) AYA and 795 (65.7%) parents. The majority of AYA (72.3%) and parents (81.9%) were female. Patients had a history of asthma (61.1%), allergic rhinoconjunctivitis (54.1%), food allergy (53.8%), atopic eczema (42.6%) and anaphylaxis (28.8%). All recommendations achieved the median score of either 'important' or 'very important'. The least supported recommendations were the use of joint clinics with both paediatric and adult physicians attending and the use of web‐based or mobile technologies for communication with the AYA. The most supported recommendation was checking that the AYA is knowledgeable and compliant with their prescribed medication. Qualitative analysis revealed conditional approval for some recommendations. Conclusions: There was agreement from patients and parents on the importance of the draft recommendations on transitional care for AYA with allergy and/or asthma and their parents. The recommendations now need to be implemented into clinical practice across Europe.